Intentional Versus Incidental Inclusion: A Comparative Analysis of Enat Bank and Addis International Bank in Advancing Women’s Economic Empowerment through Microfinance in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2026)
This review article presents a comparative analysis of two Ethiopian commercial banks—Addis International Bank (AdIB) and Enat Bank, examining their respective approaches to women's economic empowerment through microfinance. Ethiopia presents a striking paradox: women own the majority of micro and small enterprises yet face a 19-percentage-point gap in account access and are 1.5 times less likely to receive formal loans than men. Closing these gender gaps could increase Ethiopia's GDP by an estimated US$3.7 billion annually. Using institutional theory, feminist economics, and the capability approach as analytical frameworks, this review contrasts AdIB's incidental inclusion model, broad-based financial access without gender-specific mechanisms, with Enat Bank's intentional inclusion model, gender-led governance, collateral-free lending, and targeted non-financial services. The analysis reveals that Enat Bank's approach produces superior empowerment outcomes, demonstrated by its "Transformational" rating on the National Bank of Ethiopia's Women's Financial Inclusion Scorecard, 12,000 women trained in financial literacy, 1.4 billion Birr disbursed in collateral-free loans, and a 99.1% repayment rate. AdIB, despite strong financial performance with 85% profit growth, was assessed as "Neutral" or in "Emerging Awareness," indicating foundational engagement with gender inclusion. The review concludes that women's economic empowerment is not an automatic byproduct of financial inclusion but a deliberate institutional design choice. Policy recommendations include gender-lens targets for banks, collateral substitution mechanisms, governance diversification, and expanded gender bonds. This analysis contributes evidence that intentional inclusion is both socially transformative and commercially viable, offering actionable insights for financial institutions, policymakers, and development partners seeking to unlock Ethiopia's US$3.7 billion opportunity through women's economic empowerment.